Genetic identification of cytomegaloviruses in a rural population of Côte d'Ivoire. Issue 1 (December 2015) - Anoh, Augustin; Akoua-Koffi, Chantal; Couacy-Hymann, Emmanuel; Pauly, Maude; Schubert, Grit; Mossoun, Arsène; Weiss, Sabrina; Leendertz, Siv; Jarvis, Michael; Leendertz, Fabian; Ehlers, Bernhard
Abstract Background Cytomegaloviruses (CMVs) are herpesviruses that infect many mammalian species, including humans. Infection generally passes undetected, but the virus can cause serious disease in individuals with impaired immune function. Human CMV (HCMV) is circulating with high seroprevalence (60–100 %) on all continents. However, little information is available on HCMV genoprevalence and genetic diversity in subsaharan Africa, especially in rural areas of West Africa that are at high risk of human-to-human HCMV transmission. In addition, there is a potential for zoonotic spillover of pathogens through bushmeat hunting and handling in these areas as shown for various retroviruses. Although HCMV and nonhuman CMVs are regarded as species-specific, potential human infection with CMVs of non-human primate (NHP) origin, shown to circulate in the local NHP population, has not been studied. Findings Analysis of 657 human oral swabs and fecal samples collected from 518 individuals living in 8 villages of Côte d'Ivoire with generic PCR for identification of human and NHP CMVs revealed shedding of HCMV in 2.5 % of the individuals. Determination of glycoprotein B sequences showed identity with strains Towne, AD169 and Toledo, respectively. NHP CMV sequences were not detected. Conclusions HCMV is actively circulating in a proportion of the rural Côte d'Ivoire human population with circulating strains being closely related to those previously identified in non-African countries. The lack of NHP CMVs in human populations in an environment conducive to cross-species infection supports zoonotic transmission of CMVs to humans being at most a rare event.